Implementasi Metode Studio-Based Learning dalam Pengelolaan dan Prosedur Pembelajaran Studio Perancangan Arsitektur - Muhammad Rijal; Pedia Aldy (Intelektual Pustaka Media Utama, 2012)
Learning Model studio known as Studio - Based Learning (SBL) has the main features hands-on or first hand experience or learning by doing. Ideally, most of the SBL activities, either individually or in groups, conducted in a studio which was accompanied by a number of teachers / assistants. Student’s evaluation efficiently when using the method of correlational research conducted with data collection and analysis of questionnaire data with the statistics. Questions in the questionnaire were arranged by following structure: the ability of professors, lecturer’s attitudes, organization of the studio system, the ability of students, and student attitudes. Penelitian Tindakan Kelas (PTK) was conducted on students of Architectural Engineering, Faculty of Engineering UR S1 are taking courses in Architectural Design Studio 2010/2011 academic year, are 22 students. Four cycles of study procedures are planning, action, observation and reflection. Quantitive analysis was used to data analysis. The result of the research was the assessment of knowledge of the supervisor, supervisor attitudes, and the studio administration systems are good category.